Inhibitory effect of main phenolic acid components of Jacobaea cannabifolia (Less.) on inflammation caused by PM2.5 - Xu, Bao-Li; Wang, Yuan-Yuan; Jiang, Ling-Ling; Liu, Zhen; Liu, Ding-Rui; Zhao, He; Li, Shi-Liang; Wang, Xiao-Bo (Frontiers in Pharmacology, 2023)
PM2.5 is an important environmental problem threatening human health at present, which poses serious harm to human body after inhalation. J. cannabifolia is a traditional Chinese medicine which exhibits anti-inflammatory effect. This study aimed to investigate the inhibitory effect of main phenolic acid components of J. cannabifolia on inflammation caused by PM2.5. Effect of PM2.5 on cell activity and apoptosis were determined by MTT, flow cytometry and calcein AM/PI staining. PHBA, PHPAA, and mixture of PHBA and PHPAA of different concentrations were given to RAW264.7 cells pretreated with PM2.5. The effect of drugs on cellular inflammatory factors was detected by ELISA. The expressions of TLRs related signal pathway at protein and gene levels were detected by western blot and qRT-PCR. The results showed that PM2.5 had no effect on cell activity and apoptosis within the determined concentration range. PHBA and PHPAA could markly inhibit the level of IL-1β, IL-6, and TNF-α in RAW264.7 cells. Furthermore, the expressions of TLR2, TLR4, MyD88, IRAK1, TRAF6, TAK1, IKKβ, and NF-κB induced by PM2.5 were markedly inhibited by PHBA and PHPAA at protein and gene levels. This study demonstrated that PHBA and PHPAA could attenuated inflammation caused by PM2.5 through suppressing TLRs related signal pathway.